2022
DOI: 10.3389/fcell.2022.981583
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-1 modulates the 3D invasive properties of glioblastoma stem-like cells

Abstract: Glioblastoma multiforme (GBM) is a rare, yet devastating, primary brain tumor in adults. Current treatments remain generally ineffective and GBM almost invariably recurs, resulting in median survival of 15 months. This high malignancy sources notably from the resilience and invasive capabilities of tumor cells. Within GBM, exists a population of self-sustaining transformed cells with stem-like properties (GSCs), which are thought to be responsible for tumor initiation, growth, and invasion, as well as recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…Grun et al 22 found that VEGFA acted via NRP-1 to enhance epidermal CSC survival and the formation of aggressive and highly vascularized tumors. Mathilde et al 39 found that NRP-1 modulated the 3D invasive properties of glioblastoma stem-like cells, and both RNA interference-mediated silencing and CRISPR-mediated gene editing deletion of NRP-1 strongly impaired the 3D invasive properties of patient-derived cells with stem-like properties and their close localization to brain blood vessels. Another study reported that NRP-1 was overexpressed in medulloblastoma (MB) and related to the undifferentiated status of MB and that an NRP-1 inhibitor (MR438) could stimulate the differentiation of MB stem-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…Grun et al 22 found that VEGFA acted via NRP-1 to enhance epidermal CSC survival and the formation of aggressive and highly vascularized tumors. Mathilde et al 39 found that NRP-1 modulated the 3D invasive properties of glioblastoma stem-like cells, and both RNA interference-mediated silencing and CRISPR-mediated gene editing deletion of NRP-1 strongly impaired the 3D invasive properties of patient-derived cells with stem-like properties and their close localization to brain blood vessels. Another study reported that NRP-1 was overexpressed in medulloblastoma (MB) and related to the undifferentiated status of MB and that an NRP-1 inhibitor (MR438) could stimulate the differentiation of MB stem-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…Both RNA interference-mediated silencing and CRISPR-mediated gene editing deletion of NRP1 strongly impair the invasive capacity of properties of patient-derived GBM BTSCs and their close localization to brain blood vessels without affecting BTSC expansion and self-renewal. These actions of NRP1 in BTSCs may depend on the expression of the β3 subunit integrin cell-extracellular matrix adhesive receptor [101] RT-PCR of 37 glioma specimens, out of which 17 were grade IV GBM tumors, showed that NRP1 mRNA expression is higher in GBM than in non-tumoral tissue and lower-grade gliomas, and glioma patients with NRP1 overexpression (56.8%) showed a poorer prognosis indicated by reduced overall survival [102]. Moreover, NRP1 is an independent risk factor for both survival and recurrence in patients with GBMs, and high NRP1 mRNA expression is associated with shorter overall and disease-free survival, as shown by analysis of The Cancer Genome Atlas (TCGA) dataset [93].…”
Section: Glioblastomamentioning
confidence: 99%
“…18) Studies have confirmed that NRP1 is a critical molecule in regulating the invasive capacity of glioblastoma stem-like cells in vitro. 19) It has also been found that NRP1 is associated with TMZ resistance in glioblastoma. 20) However, whether NRP1 regulates the stemness and chemoresistance of glioma cells through YAP is unclear.…”
Section: Introductionmentioning
confidence: 99%